2013
DOI: 10.1105/tpc.113.111047
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Division Protein ARC3 Regulates Chloroplast FtsZ-Ring Assembly and Positioning in Arabidopsis through Interaction with FtsZ2

Abstract: Chloroplast division is initiated by assembly of a mid-chloroplast FtsZ (Z) ring comprising two cytoskeletal proteins, FtsZ1 and FtsZ2. The division-site regulators ACCUMULATION AND REPLICATION OF CHLOROPLASTS3 (ARC3), MinD1, and MinE1 restrict division to the mid-plastid, but their roles are poorly understood. Using genetic analyses in Arabidopsis thaliana, we show that ARC3 mediates division-site placement by inhibiting Z-ring assembly, and MinD1 and MinE1 function through ARC3. ftsZ1 null mutants exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(119 citation statements)
references
References 84 publications
(153 reference statements)
10
108
0
Order By: Relevance
“…Impaired division is observed in plants overexpressing FTSZ1 by <3-fold (Stokes et al, 2000;Schmitz et al, 2009). Overexpression of several other plastid division proteins also causes related but distinct abnormalities in chloroplast division, FTSZ filament organization, and chloroplast morphology (Vitha et al, 2003;Maple et al, 2007;Zhang et al, 2009Zhang et al, , 2013. By contrast, overexpression of PDV1 and/or PDV2 has the opposite effect in that it results in an increased plastid division rate and smaller and more numerous plastids per cell (Okazaki et al, 2009).…”
Section: Plastid Division Defects In Escrt and Autophagy Mutantsmentioning
confidence: 99%
“…Impaired division is observed in plants overexpressing FTSZ1 by <3-fold (Stokes et al, 2000;Schmitz et al, 2009). Overexpression of several other plastid division proteins also causes related but distinct abnormalities in chloroplast division, FTSZ filament organization, and chloroplast morphology (Vitha et al, 2003;Maple et al, 2007;Zhang et al, 2009Zhang et al, , 2013. By contrast, overexpression of PDV1 and/or PDV2 has the opposite effect in that it results in an increased plastid division rate and smaller and more numerous plastids per cell (Okazaki et al, 2009).…”
Section: Plastid Division Defects In Escrt and Autophagy Mutantsmentioning
confidence: 99%
“…Recently, S. pombe has emerged as a valuable heterologous system in which to analyze the behavior of bacterial and chloroplast FtsZ filaments as well as to test the interactions with and effects of putative FtsZ assembly regulators (Srinivasan et al, 2007(Srinivasan et al, , 2008TerBush and Osteryoung, 2012;Zhang et al, 2013). When expressed alone in S. pombe, PARC6 77-573 -mCherry fluorescence appeared diffusely localized in the cytosol (Fig.…”
Section: The Stromal Region Of Parc6 Interacts With Ftsz2mentioning
confidence: 99%
“…Furthermore, genetic analysis suggested that, unlike ARC6, which positively regulates FtsZ assembly (Vitha et al, 2003), PARC6 functions partly as a negative regulator of FtsZ assembly. Interaction assays provided evidence that this negative regulation may be mediated by interaction of the N terminus of PARC6 with the stromal division protein ARC3 (Pyke et al, 1994;Shimada et al, 2004;Maple et al, 2007), a Z-ring positioning factor recently shown to inhibit Z-ring assembly and/or promote FtsZ filament and Z-ring destabilization (TerBush and Osteryoung, 2012;Zhang et al, 2013;Johnson et al, 2015). Although the interaction of PARC6 with FtsZ was not detected previously, the significance of this finding has remained uncertain in the absence of definitive data on PARC6 topology ).…”
mentioning
confidence: 97%
“…Changes in FtsZ expression levels or assembly lead to dramatic phenotypes such Open Access *Correspondence: holzen@tamu.edu 4 Microscopy and Imaging Center, Texas A&M University, Interdisciplinary Life Sciences Building, 2257 TAMU, College Station, TX 77843-2257, USA Full list of author information is available at the end of the article as single giant chloroplasts covering entire mesophyll cells [8][9][10]. Z-ring formation/assembly depends on the balance between FtsZ and accessory chloroplast division proteins, which either stabilize (ARC6 [11,12], MinE [3,13,14]) or destabilize (ARC3 [15], PARC6 [16]) FtsZ assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement of FtsZ protofilaments in the Z-ring in chloroplasts and how they bend and proceed in chloroplast division remains unknown. Highly curved, small ring-like FtsZ assemblies, termed mini-rings, have been reported in plant chloroplasts and studied by optical microscopy [3,15,30,31]. It is hypothesized that the structural signature principles identified in these highly curved small assemblies may also play a role in the actual Z-ring.…”
Section: Introductionmentioning
confidence: 99%